Green methanol from hydrogen and carbon dioxide using geothermal energy and/or hydropower in Iceland or excess renewable electricity in Germany - Kauw, Marco; Benders, René M.J.; Visser, Cindy
The synthesis of green methanol from hydrogen and carbon dioxide can contribute to mitigation of greenhouse gasses. This methanol can be utilized as either a transport fuel or as an energy carrier for electricity storage. It is preferable to use inexpensive, reliable and renewable energy sources to provide the energy needed for the green methanol production. Iceland has a large potential for such renewable energy sources. If only geothermal CO2 may be utilized the green methanol potential in Iceland is ∼340 million L/y. When all the potentially available geothermal energy and hydropower is combined the potential becomes ∼2150 million L/y. Green methanol; Potential; CO2 recovery; Electrolysis; Transport fuel;